Four-year real-world experience of secukinumab in a large Italian cohort of axial spondyloarthritis - Ramonda, Roberta; Lorenzin, Mariagrazia; Chimenti, Maria Sole; D’Angelo, Salvatore; Marchesoni, Antonio; Selmi, Carlo; Lubrano, Ennio; Santo, Leonardo; Luchetti Gentiloni, Michele Maria; Atzeni, Fabiola; Cauli, Alberto; Manara, Maria; et al. (Frontiers in Immunology, 2024)
Objectives This study aims to evaluate in a real-life Italian multicenter cohort of axial spondyloarthritis (axSpA) (1) the 4-year effectiveness and safety of secukinumab, (2) the drug retention rate (DRR), and (3) the impact of the line of bDMARDs treatment, subtype of axSpA, and sex on achieving low disease activity (LDA) and very low disease activity (VLDA). Methods Consecutive axSpA patients receiving secukinumab between 2016 and 2023 were prospectively evaluated. Data on disease characteristics, previous/ongoing treatments, comorbidities, and follow-up duration were collected. Treatment response was evaluated at 6 and 12 months after initiation and yearly up to 48 months (T48). DRR and effectiveness outcomes were evaluated according to bDMARDs treatment, axSpA subtype, and sex. Infections and adverse events (AEs) were recorded. Results We enrolled 272 patients (48.2% male; median age, 51; 39.7% HLA-B27+; 40.4% nr-axSpA), of whom 30.9% were naïve to secukinumab. Overall, secukinumab yielded improvement in effectiveness outcomes; the naïve patients maintained lower disease activity vs. the non-naïve ones. At T48, the LDA and VLDA rates were higher in naïve patients and in male individuals. Treatment was discontinued in 104 patients due to primary/secondary loss of effectiveness and in 34 patients due to AEs. The DRR at T48 was 67.4% in the whole population, regardless of treatment line, axSpA subtype, and sex. Conclusions Secukinumab was safe and effective in all axSpA patients irrespective of treatment line, disease subtype, and sex. The patients achieved sustained 4-year remission and DRR.